2017
DOI: 10.1002/ange.201710354
|View full text |Cite
|
Sign up to set email alerts
|

The Divergent Dimerization Behavior of N‐Substituted Dicyanomethyl Radicals: Dynamically Stabilized versus Stable Radicals

Abstract: Herein, we demonstrate that the dimerization behavior of amine‐substituted dicyanomethyl radicals can be switched from σ‐ to π‐dimerization simply by varying the electron‐donating substituents. For dicyanomethyl radicals with a 4,4′‐ditolylamine (DT.) or a phenothiazine (PT.) substituent, the monomeric radical form and the corresponding dimer connected by a reversible C−C bond (σ‐dimer) are in equilibrium in solution. On the other hand, the radical with the julolidine skeleton (JD.) does not undergo σ‐dimeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Therefore, controllable modulation of the stability of the radical intermediates is of vital importance to optimize the performance of the organic electrode materials. Previous reports and our work , showed that π–π and p−π conjugation interactions could contribute to delocalize the energy density of the unpaired electrons and the steric effect could restrict intermolecular electron self-exchange behavior. On the basis of this idea, rigid aromatic rings (such as formazanate complexes, trioxotriangulene, and triphenylmethane) were often used as blocks to provide conjugation structure and steric effect to tune the stability of the radical intermediates.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, controllable modulation of the stability of the radical intermediates is of vital importance to optimize the performance of the organic electrode materials. Previous reports and our work , showed that π–π and p−π conjugation interactions could contribute to delocalize the energy density of the unpaired electrons and the steric effect could restrict intermolecular electron self-exchange behavior. On the basis of this idea, rigid aromatic rings (such as formazanate complexes, trioxotriangulene, and triphenylmethane) were often used as blocks to provide conjugation structure and steric effect to tune the stability of the radical intermediates.…”
Section: Introductionsupporting
confidence: 54%
“…As is known, the combination of donor-acceptor interaction and π-conjugation may efficiently redshift the fluorescence of fluorochrome (24,25). Meanwhile, the good planarity could promote intermolecular π−π stacking interaction (26,27), thereby decreasing the solubility and realizing antidiffusion imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding CCDC identifier and label used in this work are listed below the radical dimer. The following crystal structures were used: SAXPOW01, , SAXPOW05, , SAXPOW06, , ITULIT01, , JASKEW03, , and DESJET , …”
Section: Results and Discussionmentioning
confidence: 99%
“…For the Wu−Yang potential reconstructions the following convergence criteria were used: First, the overall integrated density error is below 1.0 × 10 −5 electrons. Second, The following crystal structures were used: SAXPOW01, 62,63 SAXPOW05, 64,65 SAXPOW06, 64,66 ITULIT01, 67,68 JASKEW03, 28,69 and DESJET 70,71 The Journal of Physical Chemistry C the density error between two iterations changes less than 1.0 × 10 −7 electrons. The van Leeuwen−Baerends reconstruction was limited to 5000 cycles.…”
Section: Computational Detailsmentioning
confidence: 99%